PENERAPAN DATA MINING UNTUK REKOMENDASI PAKET FOTO PRIWED MENGGUNAKAN ALGORITMA APRIORI - Ifan Farimulyadi; Zaehol Fatah (Jurnal Riset Teknik Komputer, 2025)
SM Wedding Decoration is a place that provides services to take care of everything related to weddings. For example, wedding decorations, wedding organizers, and wedding planners. SM Wedding Decoration has several wedding packages that can be offered to customers.  The large number of packages available makes prospective brides or customers confused about which wedding package is suitable for their wedding. The a priori algorithm method is used in this research to find recommendations for wedding packages based on existing transaction data and to improve company strategies and sales of other wedding packages. The Apriori algorithm is used to help computers learn patterns of association rules. This algorithm looks for a group of things that match the given criteria or order and have a certain frequency value. From this research, customers tend to order Photographer & Documentation and MUA → Deluxe packages more often, and these orders account for 44% of all package order transaction data. Transaction data for ordering the MUA→Deluxe Package was 41.3%. Photographer & Documentation package transaction data → Deluxe Package is 41.2%. And transaction data for ordering the MUA package → Premium Deluxe Package is 41.3%.